ПЕДАГОГІЧНІ ПРОБЛЕМИ ФОРМУВАННЯ ЗДОРОВОГО СПОСОБУ ЖИТТЯ УЧНІВСЬКОЇ ТА СТУДЕНТСЬКОЇ МОЛОДІ - Бордун, Л.; Джусь, Г.; Корінчак, Л. (Збірник наукових праць Уманського державного педагогічного університету, 2019)
У статті проаналізовано основні педагогічні проблеми збереження здоров’я школярів та студентської молоді, профілактики шкідливих звичок, статевого виховання. Обґрунтовано передумови покращення стану здоров’я підростаючого покоління. The article deals with the problem of rational use of physical exercises in educational and labour activity of students. Special attention is paid to the specific ways of solving this problem taking into account age psychological and physiological peculiarities of pupils and students. The results of the experiment have proved that intensively normal physical load has positive influence on the level of mental activity, averts overtiredness and improves students’ general state.